A core-shell structure aerogel, a preparation method thereof and application thereof in fire-resistant bricks
Patent Information
- Application Number
- CN202411340279.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-09-25
AI Technical Summary
[0004]本发明的目的在于提供一种核壳结构气凝胶的制备方法,以解决背景技术中提及的二氧化硅气凝胶耐热性差、强度低的问题
[0023] This invention first modifies ordinary silica aerogel by carboxylation to obtain carboxylated silica aerogel. Then, using the carboxylated silica aerogel as a precursor, a silica/zirconium dioxide composite aerogel with a high-temperature resistant core-shell structure is prepared by adopting a "Zr-coated Si" strategy. Compared with unmodified silica aerogel, the carboxylated silica aerogel as a precursor can uniformly and firmly adsorb zirconium hydroxide formed by the hydrolysis of zirconium oxychloride. Furthermore, by controlling the amount of carboxylated silica aerogel, a zirconium dioxide gel is formed on the framework of the silica aerogel, resulting in a core-shell structure aerogel with superior heat resistance and insulation properties. This solves the problems of structural collapse and loss of insulation performance of ordinary silica aerogel at high temperatures, and also solves the problem that traditional silica aerogel cannot be calcined at high temperatures simultaneously with refractory brick raw materials.
Smart Images

Figure CN119430957B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal insulation materials technology, specifically relating to a core-shell structured aerogel, its preparation method, and its application in refractory bricks. Background Technology
[0002] As one of the insulation materials for industrial kilns, refractory bricks not only need to resist the erosion and friction of materials in the kiln, but also play an important role in heat insulation, heat preservation, and protection of the kiln body. Therefore, the development of high-strength, low-thermal-conductivity refractory bricks is conducive to reducing heat loss, extending the service life of the kiln body, significantly reducing the fuel supply required for industrial kilns, and reducing standard coal consumption. This is of great significance for enterprises to reduce carbon emissions and improve economic benefits. When improving refractory bricks using existing technologies, the main improvement methods are as follows: 1. Constructing low thermal conductivity refractory bricks with multi-layer composite structures. Utility model patent CN211977551 U discloses a new type of spinel brick for cement rotary kilns, proposing a new composite structure of a working layer, insulation layer, and heat insulation layer. However, the large difference in thermal expansion coefficients among the materials in each layer of this structure easily causes high-temperature thermal shock material fracture, resulting in a significant loss in flexural strength compared to traditional heat insulation materials. 2. Introducing lightweight aggregates. Invention patent CN116803956A discloses a method for preparing low thermal conductivity aluminosilicate porous refractory bricks. This invention introduces heat-insulating lightweight aggregates, using a mullite working layer to coat the lightweight aggregates, then pouring the mixed aggregates into a mold for drying and calcination to prepare a new type of refractory brick. Although the introduction of lightweight aggregates can increase the heat transfer path and reduce the outward heat transfer speed, the product has poor wear resistance and strength. Therefore, how to balance the compressive strength and low thermal conductivity of refractory bricks is a technical problem that urgently needs to be solved.
[0003] Silica aerogels are characterized by low density, light weight, large specific surface area, and ultra-low thermal conductivity, making them widely used in aerospace, military, and other fields. With breakthroughs in low-cost silica aerogel technology, their application in civil building insulation is becoming increasingly widespread, thus making their application in refractory bricks feasible. However, the heat resistance temperature of existing silica aerogels is only around 650℃. At higher temperatures, the pore structure of silica aerogels undergoes crystal transformation, leading to collapse and a significant reduction in insulation performance. This fails to meet the application requirements of industrial kilns with production temperatures of approximately 1300℃. Therefore, it is not feasible to directly blend existing silica aerogels with refractory brick raw materials for integral calcination. Further improvements to existing silica aerogels are needed to enhance their compressive strength, heat resistance, and reduce their thermal conductivity. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing core-shell structured aerogels to solve the problems of poor heat resistance and low strength of silica aerogels mentioned in the background art.
[0005] Another objective of this invention is to provide a core-shell structured silica and zirconium dioxide composite aerogel with higher heat resistance, strength, and thermal insulation properties.
[0006] Another object of the present invention is to provide an application of core-shell structured aerogel in refractory bricks.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] A method for preparing a core-shell structured aerogel includes the following steps:
[0009] Zirconium oxychloride was added to an aqueous ethanol solution at room temperature and completely hydrolyzed to form a homogeneous solution. Then, carboxylated silica aerogel was added and stirred for 2-10 hours to ensure uniform dispersion of the silica aerogel. A gelling agent was then added to form a sol solution. After sealing and aging, a wet gel was obtained. The wet gel was then submerged in n-hexane to perform solvent replacement, with the replacement occurring 3-5 times. After supercritical CO2 drying and pulverization, a core-shell structured aerogel was obtained.
[0010] Further, the mass ratio of zirconium oxychloride, aqueous ethanol solution, carboxylated silica aerogel, and gelling agent is 1:5-6:4-5:0.5-1; the concentration of the aqueous ethanol solution is 97wt%; and the gelling agent is propylene oxide or citric acid.
[0011] Furthermore, the carboxylated silica aerogel is prepared by the following steps:
[0012] γ-aminopropyltriethoxysilane and succinic anhydride were added to N,N-dimethylformamide and stirred. The mixture was stirred and reacted at room temperature under nitrogen protection for 8-10 hours. Then, calcined silica aerogel and deionized water were added and stirred thoroughly to disperse the mixture. The reaction was continued at room temperature for 5-6 hours. After centrifugation, washing with anhydrous ethanol, and drying, carboxylated silica aerogel was obtained. The amino group of γ-aminopropyltriethoxysilane reacted with succinic anhydride at room temperature to obtain a siloxane containing a carboxyl group. Then, the carboxyl group was grafted onto the surface of the silica aerogel by hydrolysis of the siloxane and condensation with the silica aerogel.
[0013] Further, the ratio of γ-aminopropyltriethoxysilane, succinic anhydride, N,N-dimethylformamide, calcined silica aerogel, and deionized water is 2-2.1 g: 1-1.1 g: 50 mL: 0.8-1 g: 2 mL; the calcined silica aerogel is obtained by calcining silica aerogel at 500-550℃ for 3-4 hours. Under high-temperature calcination, the number of hydroxyl groups on the surface of silica aerogel increases significantly, which is beneficial for subsequent polycondensation and bonding with carboxyl-containing siloxanes.
[0014] Furthermore, the aging temperature is 50-60℃, and the aging time is 2-4 hours.
[0015] Furthermore, the temperature for supercritical CO2 drying is 30-45℃, the pressure is 6-8MPa, and the drying time is 3-5h.
[0016] A core-shell aerogel was prepared by the above method.
[0017] The application of a core-shell structured aerogel in refractory bricks includes the following steps:
[0018] Step S1: Soak the core-shell aerogel in an organic solvent to allow the organic solvent to fully fill the pores of the core-shell aerogel. Then, add refractory brick raw materials with a particle size of 0.05-0.2 mm and stir thoroughly for 30 minutes until a homogeneous aerogel-free powder is formed. Then, add the remaining refractory brick raw materials and stir thoroughly. Finally, add bentonite solution and continue stirring for 30 minutes to obtain the refractory brick mixture.
[0019] Step S2: Pour the refractory brick mixture into a mold and mold it under a pressure of 70-90MPa. After demolding, the refractory brick blank is obtained. The refractory brick blank is transferred into a kiln and calcined at a temperature of 1200-1300℃ for 24 hours. After cooling after exiting the kiln, aerogel-modified refractory bricks are obtained.
[0020] Furthermore, the mass percentage of each component in the refractory brick mixture is as follows: 0.5-3% core-shell aerogel, 2.5-15% organic solvent, 80-90% refractory brick raw material, and 2-7% bentonite solution, with the sum of the mass percentages of the above components being 100%; the organic solvent is acetone or N-methylpyrrolidone; and the concentration of the bentonite solution is 3-8 wt%.
[0021] Furthermore, the refractory brick raw material comprises the following components by weight percentage: 70-80% bauxite, 10-15% silicon carbide, and the remainder is made up to 100% with white clay; the refractory brick raw material with a particle size of 0.05-0.2mm accounts for 10-25% of the total mass.
[0022] The beneficial effects of this invention are:
[0023] This invention first modifies ordinary silica aerogel by carboxylation to obtain carboxylated silica aerogel. Then, using the carboxylated silica aerogel as a precursor, a silica / zirconium dioxide composite aerogel with a high-temperature resistant core-shell structure is prepared by adopting a "Zr-coated Si" strategy. Compared with unmodified silica aerogel, the carboxylated silica aerogel as a precursor can uniformly and firmly adsorb zirconium hydroxide formed by the hydrolysis of zirconium oxychloride. Furthermore, by controlling the amount of carboxylated silica aerogel, a zirconium dioxide gel is formed on the framework of the silica aerogel, resulting in a core-shell structure aerogel with superior heat resistance and insulation properties. This solves the problems of structural collapse and loss of insulation performance of ordinary silica aerogel at high temperatures, and also solves the problem that traditional silica aerogel cannot be calcined at high temperatures simultaneously with refractory brick raw materials.
[0024] This invention utilizes the sacrificial template method, filling core-shell aerogel with an organic solvent, and then successfully mixing the lightweight core-shell aerogel with refractory brick raw materials of similar particle size through electrostatic adsorption. The remaining refractory brick raw materials are then added and mixed evenly. Bentonite solution is used as a binder to bond the materials together. After high-pressure molding and high-temperature firing, refractory bricks are obtained. This solves the problem of the lightweight aerogel failing to integrate well with refractory brick raw materials. Furthermore, by rationally controlling the addition amount of core-shell aerogel to 0.5-3% of the total refractory brick mixture, the resulting refractory bricks possess high strength, high-temperature resistance, and low thermal conductivity.
[0025] The refractory bricks produced by this invention significantly improve their thermal insulation performance with limited strength loss compared to existing refractory bricks, and have the dual effects of thermal insulation and mechanical strength, breaking the problem that traditional low thermal conductivity refractory bricks cannot simultaneously achieve both strength and thermal insulation. Attached Figure Description
[0026] The invention will now be further described with reference to the accompanying drawings.
[0027] Figure 1 These are actual images of the refractory brick samples prepared in Example 6, Comparative Example 4, and Comparative Example 6 of the present invention. The sample on the left is the refractory brick sample prepared in Comparative Example 4, the sample in the middle is the refractory brick sample prepared in Comparative Example 6, and the sample on the right is the refractory brick sample prepared in Example 6. Detailed Implementation
[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0029] Example 1
[0030] This embodiment provides a core-shell structured aerogel, including the following steps:
[0031] Step A1: Add 20g of γ-aminopropyltriethoxysilane and 10g of succinic anhydride to 500mL of N,N-dimethylformamide and stir to mix. Stir and react for 8h under nitrogen protection and at room temperature. Then add 8g of silica aerogel that has been calcined at 500℃ for 3h and 20mL of deionized water and stir to disperse thoroughly. Continue stirring and react for 5h at room temperature. After centrifugation, wash with anhydrous ethanol and dry, obtain carboxylated silica aerogel.
[0032] Step A2: At room temperature, 1g of zirconium oxychloride was added to 5g of 97% ethanol aqueous solution for complete hydrolysis to form a homogeneous solution. Then, 4g of carboxylated silica aerogel was added and stirred for 2h to uniformly disperse the silica aerogel. Then, 0.5g of gelling agent was added to form a sol solution. After aging in a closed environment at 50℃ for 4h, a wet gel was obtained. The wet gel was then submerged in n-hexane to perform solvent replacement, and the replacement was performed 3 times. The gel was then dried with supercritical CO2 at 30℃ and 6MPa for 5h. After pulverization, a core-shell structured aerogel was obtained.
[0033] Example 2
[0034] This embodiment provides a core-shell structured aerogel, including the following steps:
[0035] Step A1: 20.5g of γ-aminopropyltriethoxysilane and 10.5g of succinic anhydride were added to 500mL of N,N-dimethylformamide and stirred. The mixture was stirred and reacted at room temperature under nitrogen protection for 9h. Then, 9g of silica aerogel that had been calcined at 520℃ for 3.5h and 20mL of deionized water were added and stirred and dispersed thoroughly. The mixture was stirred and reacted at room temperature for another 6h. After centrifugation, washing with anhydrous ethanol, and drying, carboxylated silica aerogel was obtained.
[0036] Step A2: At room temperature, 1g of zirconium oxychloride was added to 6g of 97% ethanol aqueous solution for complete hydrolysis to form a homogeneous solution. Then, 4.5g of carboxylated silica aerogel was added and stirred for 6h to uniformly disperse the silica aerogel. 0.8g of gelling agent was then added to form a sol solution. After aging in a sealed environment at 55℃ for 3h, a wet gel was obtained. The wet gel was then submerged in n-hexane to perform solvent replacement, with 4 replacement cycles. After supercritical CO2 drying at 38℃ and 7MPa for 4h, the gel was pulverized to obtain a core-shell structured aerogel.
[0037] Example 3
[0038] This embodiment provides a core-shell structured aerogel, including the following steps:
[0039] Step A1: Add 21g of γ-aminopropyltriethoxysilane and 11g of succinic anhydride to 500mL of N,N-dimethylformamide and stir to mix. Stir and react for 10h under nitrogen protection and at room temperature. Then add 10g of silica aerogel that has been calcined at 550℃ for 4h and 20mL of deionized water and stir to disperse thoroughly. Continue stirring and react for 6h at room temperature. After centrifugation, wash with anhydrous ethanol and dry, obtain carboxylated silica aerogel.
[0040] Step A2: At room temperature, 1g of zirconium oxychloride was added to 6g of 97% ethanol aqueous solution for complete hydrolysis to form a homogeneous solution. Then, 5g of carboxylated silica aerogel was added and stirred for 10h to uniformly disperse the silica aerogel. 1g of gelling agent was then added to form a sol solution. After aging in a closed environment at 60℃ for 2h, a wet gel was obtained. The wet gel was then submerged in n-hexane to perform solvent replacement, with 5 replacement cycles. After supercritical CO2 drying at 45℃ and 8MPa for 3h, the gel was pulverized to obtain a core-shell structured aerogel.
[0041] Comparative Example 1
[0042] The difference between this comparative example and Example 3 is that step A1 is not performed, and in step A2, untreated silica aerogel is used to replace carboxylated silica aerogel in an equal amount. All other raw materials and steps are the same.
[0043] Comparative Example 2
[0044] The difference between this comparative example and Example 3 is that the amount of carboxylated silica aerogel used in step A2 was adjusted to 3g, while the amounts of other raw materials and steps were the same.
[0045] Comparative Example 3
[0046] The difference between this comparative example and Example 3 is that the amount of carboxylated silica aerogel used in step A2 was adjusted to 6g, while the amounts of other raw materials and steps were the same.
[0047] The specific surface area, average pore size, and thermal conductivity of the aerogels prepared in Examples 1-3 and Comparative Examples 1-3 were tested, and the results are shown in Table 1:
[0048] Table 1
[0049] <![CDATA[Specific surface area m 2 / g]]> 450 471 487 464 384 492 Average pore size (nm) 19.26 20.42 21.45 21.73 17.74 21.54 Thermal conductivity W / (m·K) 0.045 0.047 0.049 0.038 0.056 0.059 Applicable temperature (°C) 1300 1300 1300 900 1300 1100
[0050] As shown in Table 1, the addition of carboxylated silica aerogel can improve the specific surface area and pore structure of core-shell aerogels. Although the specific surface area and average pore size increase with the increase of the amount of carboxylated silica aerogel added, the thermal conductivity of the core-shell structure increases instead. Therefore, it is necessary to control the amount of carboxylated silica aerogel to prevent negative impact on the thermal insulation performance of core-shell aerogels.
[0051] Example 4
[0052] This embodiment provides an application of core-shell structured aerogel in refractory bricks, including the following steps:
[0053] Step S1: Soak 3 parts by weight of the core-shell structured aerogel prepared in Example 1 in 15 parts by weight of acetone, then add 20 parts by weight of refractory brick raw material with a particle size range of 0.05-0.2 mm and stir thoroughly for 30 min until a homogeneous aerogel-free powder is formed. Then add the remaining 60 parts by weight of refractory brick raw material with the remaining particle size and stir thoroughly. Finally, add 2 parts by weight of 8 wt% bentonite solution and continue stirring for 30 min to obtain the refractory brick mixture. The refractory brick raw material includes the following components by weight percentage: 70% bauxite, 10% silicon carbide, and 20% white clay.
[0054] Step S2: Pour the refractory brick mixture into a mold and press it into shape under a pressure of 70 MPa. After demolding, a refractory brick blank is obtained. The refractory brick blank is transferred into a kiln and calcined at a temperature of 1200℃ for 24 hours. After cooling after exiting the kiln, aerogel-modified refractory bricks are obtained.
[0055] Example 5
[0056] This embodiment provides an application of core-shell structured aerogel in refractory bricks, including the following steps:
[0057] Step S1: 1.8 parts by weight of the core-shell structured aerogel prepared in Example 2 is soaked in 8.2 parts by weight of N-methylpyrrolidone. Then, 17 parts by weight of refractory brick raw material with a particle size range of 0.05-0.15 mm is added and stirred thoroughly for 30 min until a homogeneous aerogel-free powder state is achieved. Then, the remaining 68 parts by weight of refractory brick raw material with the specified particle size is added and stirred thoroughly. Finally, 5 parts by weight of a 6 wt% bentonite solution is added and stirred for another 30 min to obtain the refractory brick mixture. The refractory brick raw material includes the following components by weight percentage: 75% bauxite, 12% silicon carbide, and 13% white clay.
[0058] Step S2: Pour the refractory brick mixture into a mold and press it into shape under a pressure of 80 MPa. After demolding, a refractory brick blank is obtained. The refractory brick blank is transferred into a kiln and calcined at a temperature of 1250℃ for 24 hours. After cooling after exiting the kiln, aerogel-modified refractory bricks are obtained.
[0059] Example 6
[0060] This embodiment provides an application of core-shell structured aerogel in refractory bricks, including the following steps:
[0061] Step S1: 0.5 parts by weight of the core-shell aerogel prepared in Example 3 is soaked in 2.5 parts by weight of acetone. Then, 9 parts by weight of refractory brick raw material with a particle size range of 0.05-0.08 mm is added and stirred thoroughly for 30 minutes until a homogeneous aerogel-free powder is formed. Then, 81 parts by weight of the remaining refractory brick raw material with the specified particle size is added and stirred thoroughly. Finally, 7 parts by weight of a 3 wt% bentonite solution is added and stirred for another 30 minutes to obtain the refractory brick mixture. The refractory brick raw material includes the following components by weight percentage: 80% bauxite, 15% silicon carbide, and 5% white clay.
[0062] Step S2: Pour the refractory brick mixture into a mold and press it under a pressure of 90 MPa. After demolding, a refractory brick blank is obtained. The refractory brick blank is transferred into a kiln and calcined at a temperature of 1300℃ for 24 hours. After cooling after removal from the kiln, aerogel-modified refractory bricks are obtained, such as... Figure 1 The actual object is shown on the right.
[0063] Comparative Example 4
[0064] The difference between this comparative example and Example 6 is that the core-shell aerogel prepared in Example 3 is not added in step S1; all other raw materials and steps are the same. Figure 1 The actual object is shown on the left.
[0065] Comparative Example 5
[0066] The difference between this comparative example and Example 6 is that acetone soaking is not used in step S1. Instead, the core-shell aerogel prepared in Example 3 is directly mixed with refractory brick raw materials of the corresponding particle size. All other steps are the same.
[0067] Comparative Example 6
[0068] The difference between this comparative example and Example 6 is that the amount of the core-shell aerogel prepared in Example 3 is increased to 5.2 parts by weight in step S1, while the other raw materials and steps are the same. Figure 1 The actual object shown in the middle.
[0069] According to GB / T 5072-2008 standard, the bulk density, porosity, compressive strength, load softening temperature, and thermal conductivity of the refractory bricks prepared in Examples 4-6 and Comparative Examples 4-6 were tested. Each group of refractory bricks was placed in a reheat furnace and held at 1200℃ for 120 min. Immediately after the holding period, the temperature of each group of refractory bricks was measured. The test results are shown in Table 2.
[0070] Table 2
[0071]
[0072] As can be seen from the data in Table 2, the refractory bricks prepared in Examples 4-6 exhibit higher compressive strength and lower thermal conductivity, possessing the characteristics of high strength, high temperature resistance, and low thermal conductivity; Figure 1 It can be seen that, compared with Example 6, Comparative Example 6 used an excessive amount (about 5% of the total amount of refractory brick mixture) of core-shell structured aerogel, which led to an increase in the porosity of the refractory brick and a significant decrease in compressive strength. Therefore, it is necessary to strictly control the amount of core-shell structured aerogel within the scope of this invention.
[0073] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0074] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a core-shell structured aerogel, characterized in that, Includes the following steps: Zirconium oxychloride was hydrolyzed in an aqueous ethanol solution at room temperature, followed by the addition of carboxylated silica aerogel and stirring for 2-10 hours. A gelling agent was then added to form a sol solution, which was sealed and aged to obtain a wet gel. The wet gel was then subjected to solvent replacement with n-hexane 3-5 times, dried with supercritical CO2, and broken down to obtain a core-shell structured aerogel. The mass ratio of zirconium oxychloride, aqueous ethanol solution, carboxylated silica aerogel, and gelling agent was 1:5-6:4-5:0.5-1. By controlling the amount of carboxylated silica aerogel, a zirconium dioxide gel was formed on the framework of the silica aerogel.
2. The method for preparing a core-shell structured aerogel according to claim 1, characterized in that, The concentration of the ethanol aqueous solution is 97 wt%; the gelling agent is propylene oxide or citric acid.
3. The method for preparing a core-shell structured aerogel according to claim 1, characterized in that, The carboxylated silica aerogel is prepared by the following steps: γ-aminopropyltriethoxysilane and succinic anhydride were added to N,N-dimethylformamide and stirred. The mixture was stirred and reacted at room temperature under nitrogen protection for 8-10 hours. Then, calcined silica aerogel and deionized water were added and stirred and dispersed. The mixture was stirred and reacted at room temperature for another 5-6 hours. After centrifugation, washing with anhydrous ethanol, and drying, carboxylated silica aerogel was obtained.
4. The method for preparing a core-shell structured aerogel according to claim 3, characterized in that, The ratio of γ-aminopropyltriethoxysilane, succinic anhydride, N,N-dimethylformamide, calcined silica aerogel, and deionized water is 2-2.1g:1-1.1g:50mL:0.8-1g:2mL; the calcined silica aerogel is obtained by calcining silica aerogel at a temperature of 500-550℃ for 3-4 hours.
5. The method for preparing a core-shell structured aerogel according to claim 1, characterized in that, The aging temperature is 50-60℃, and the aging time is 2-4 hours.
6. The method for preparing a core-shell structured aerogel according to claim 1, characterized in that, The supercritical CO2 drying temperature is 30-45℃, the pressure is 6-8MPa, and the drying time is 3-5h.
7. A core-shell aerogel, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.
8. The application of a core-shell structured aerogel according to claim 7 in refractory bricks, characterized in that, Includes the following steps: Step S1: Soak the core-shell structured aerogel in an organic solvent, then add refractory brick raw materials with a particle size of 0.05-0.2 mm and stir until uniform. Then add the remaining refractory brick raw materials and stir until uniform. Finally, add bentonite solution and continue stirring until uniform to obtain refractory brick mixture. Step S2: Pour the refractory brick mixture into a mold and press it into shape under a pressure of 70-90MPa. After demolding, the refractory brick blank is obtained. The refractory brick blank is transferred into a kiln and calcined at a temperature of 1200-1300℃ for 24 hours. After cooling after being removed from the kiln, the refractory brick is obtained.
9. The application of a core-shell structured aerogel according to claim 8 in refractory bricks, characterized in that, The mass percentages of each component in the refractory brick mixture are as follows: core-shell aerogel 0.5-3%, organic solvent 2.5-15%, refractory brick raw material 80-90%, and bentonite solution 2-7%; the organic solvent is acetone or N-methylpyrrolidone; and the concentration of the bentonite solution is 3-8 wt%.
10. The application of a core-shell structured aerogel according to claim 8 in refractory bricks, characterized in that, The refractory brick raw material comprises the following components by weight percentage: 70-80% bauxite, 10-15% silicon carbide, and the remainder is made up to 100% with white clay; the refractory brick raw material with a particle size of 0.05-0.2mm accounts for 10-25% of the total mass.
Citation Information
Patent Citations
Preparation method of low-thermal-conductivity aluminum-silicon porous structure refractory brick
CN116803956A
Novel spinel brick for rotary cement kiln
CN211977551U
Preparation method of zirconium oxide-silicon oxide composite aerogel
CN103214034A
Silicon-zirconium composite aerogel and preparation method thereof
CN117482858A